OP0180 Type i interferon is produced by non-haematopoietic tissue resident cells but not pdcs in pre-clinical autoimmunity and sle. (12th June 2018) - Psarras, A; Alase, A.; Antanaviciute, A.; Carr, I.; Wittmann, M.; Tsokos, G.; Emery, P.; Vital, E.M.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is characterised by persistently high type I interferon (IFN) activity. Plasmacytoid dendritic cells (pDCs) produce large amounts of IFNs in viral infection, although these immunogenic properties are usually strictly regulated. In vitro, pDCs are responsive to nucleic acids and they have therefore been postulated to be the main source of type I IFNs in SLE. However, their function is not fully established in human SLE. Objectives: To investigate the dysregulated IFN axis in patients with pre-clinical autoimmunity and SLE. Methods: Patients with SLE who met 2012 ACR/SLICC criteria were recruited. We also recruited healthy controls (HC) and therapy-naïve individuals presenting with ANA and 1–2 clinical symptoms, but not meeting ACR/SLICC criteria, of whom 17% progressed to SLE (At-Risk). IFN activity was evaluated by measuring a score of IFN-responsive genes in the PBMCs using TaqMan. pDCs were immunophenotyped as well as studied in vitro for production of proinflammatory cytokines and induction of T cell responses using flow cytometry. pDCs were sorted and sequenced using high-sensitive RNA sequencing. IFN expression was visualised in skin biopsies using in situ hybridisation. Keratinocytes were isolated from fresh skin biopsies and cultured in vitro ; IFN production was measured by qPCR and ELISA. Results: Most of the SLE and At-Risk patients had increased IFN activity, which correlated with disease activity and clinical features. In contrast, circulating pDCs were decreased in both SLE and At-Risk patients and their numbers did not correlate with any clinical features or IFN status. In vitro stimulation revealed that pDCs from SLE and At-Risk patients could not produce IFN-α and TNF-α upon stimulation with TLR9 or TLR7 agonists. In addition, they induced significantly less T cell activation and proliferation compared to HC pDCs. RNA-seq data analysis showed an upregulation of IFN-responsive genes in most of the SLE and At-Risk pDCs but not transcripts of any IFN subtypes. Other upregulated pathways were related to immune regulation and senescence. Phenotypically, SLE pDCs were characterised by upregulation of regulatory receptors and increased telomeric erosion. In situ hybridization revealed high IFN expression in the epidermis but not in lymphocyte-infiltrating areas of lesional biopsies from SLE patients. High expression of IFN was also observed in epidermis of At-Risk individuals without any signs of cutaneous inflammation. In vitro stimulation of freshly isolated keratinocytes also showed a notable increase in IFN production. Conclusions: In SLE, non-haematopoietic tissue resident cells are a dominant source of IFN and this is present prior to clinically overt disease. Meanwhile, the professional IFN-producing pDCs have lost their immunogenic properties. These findings suggest an important role for tissue resident cells in autoimmunity and may facilitate novel therapeutic interventions. Disclosure of Interest: None declared